Justifications for a Perceptually Oriented Theory of Language - Ruthrof, Horst (Signs - International Journal of Semiotics, 2009)
The paper identifies three dominant traditions in the theorisation of language responsible for a 19th century bias towards formalisation. What is glaringly missing, the paper suggests, is iconicity in Peirce’s sense. This is seen as the main reason why our existing paradigms have failed to address the crucial relation between language and perception. First, I offer a series of justifications in support of a perceptually oriented theory of natural language. Second, I present redefinitions of the linguistic sign, meaning, reference, deixis and other aspects of language as necessary preconditions for a reconciliation of percepts and verbal expressions. Such a theory hinges on the claim that culturally saturated discourse can function as it does only because the schematic skeleton of its signifiers is brought to life in each meaning event by a socially monitored process of activation by iconic, nonverbal semiosis.